Coagulation-Adsorption of Suspended Solids and Residual Oil from Palm Oil Mill Effluent using Chitosan - Abdul Latif bin Ahmad; S. Sumathi; Bassim H. Hameed (Department of Chemical Engineering, Universitas Gadjah Mada, 2004)
A bench-scale study of suspended solids and residue oil removal from palm oil mill effluent (POME) was conducted. Residual oil and suspended solids constitute a severe problem in POME treatments. Preliminary analysis showed that PO ME contains about 4,000 mg/! of residual oil and 18,000 mg/! of suspended solids. These values are very high compared to the maximum limit allowed by the Malaysian Department of Environment (DOE) at about 50 mg/I for residual oil and 400 mg/I for suspended solids. Chitosan, poly-p (1-4)2-acetamido-2-deoxy-D-glucose (N-deacetylated), is a biodegradable cationic biopolymer obtained by extensive deal«tylation of chitin. Chitosan was applied as a coagulant to sequester the suspended solid and as an adsorbent to adsorb the residual oil. In this study, the effects were analyzed using the jar test apparatus as the standard procedure for bench-scale testing. The effects of experimental parameters, such as dosage of chitosan, mixing time, mixing rate, sedimentation time, and pH, were performed to study and manipulate the optimum conditions. Results showed that a combination of 0.5 g dosage of chitosan, 15 min of mixing time, 100 rpm of mixing rate, and 30 min of sedimentation at pH 5 provide the most suitable condition for the removal of POME residual oil and suspended solids. The removal percentage for residual oil was 99% whereas for suspended solids the value was 250 mg/!. The Fourier transform infrared (FTIR) spectroscopy study proved the adsorption of residual oil on chitosan.